2013
DOI: 10.1111/j.1532-849x.2012.00915.x
|View full text |Cite
|
Sign up to set email alerts
|

Masking Ability of Zirconia with and without Veneering Porcelain

Abstract: While zirconium oxide coping material alone has a degree of masking ability, the resulting color of a restoration can be further modified with the veneering porcelain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…When veneering ceramics were layered above TZP cores, TP for all shades decreased to values from 1 to 3 exhibiting minimal translucency. TZP particles are slightly bigger than wavelength of visible light and also have different refractive indexes than the matrix, giving maximal scattering effect and opacity, which explains the lack of translucency in other words, the masking effect of TZP 13,17) . In addition Choi et al reported that the resulting color of restoration can be modified with the veneering porcelain, which is also in agreement with our conclusion 13) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When veneering ceramics were layered above TZP cores, TP for all shades decreased to values from 1 to 3 exhibiting minimal translucency. TZP particles are slightly bigger than wavelength of visible light and also have different refractive indexes than the matrix, giving maximal scattering effect and opacity, which explains the lack of translucency in other words, the masking effect of TZP 13,17) . In addition Choi et al reported that the resulting color of restoration can be modified with the veneering porcelain, which is also in agreement with our conclusion 13) .…”
Section: Discussionmentioning
confidence: 99%
“…If we were to indicate the cause of color difference between the core colors, it would be the lack of the shade base layer which affected L* and a* for A1 and L* and b* for A4. When properly veneered, colored TZP frameworks are said to produce clinically acceptable color match and have the capacity to mask a dark background such as a dark tooth or core buildup material 13,31) . Our results are consistent with studies reporting that the veneering ceramic is what modifies the final color of ACR 9,13) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations